Parental Holding terhadap Distress Anak Selama Prosedur Insertion Intra Vena (IV) - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus; J, Harsismanto (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of parental holding on children's distress during the intravenous (IV) insertion procedure in the pediatric inpatient room of Dr. M. Yunus Hospital, Bengkulu. The research method used was quantitative, with a quasi-experimental approach using the One Group Pretest-Posttest design. The results showed that there was a significant effect of parental holding before and after on children's distress during the intravenous (IV) insertion procedure in the pediatric inpatient room of Dr. M. Yunus Hospital, Bengkulu with a diastolic p-value of 0.000 (p <0.05). In conclusion, there is an effect of parental holding on children's distress during the intravenous (IV) insertion procedure in the pediatric inpatient room of Dr. M. Yunus Hospital, Bengkulu. Keywords: Child Distress, Intravenous Insertion, Parental Holding